Efektivitas Ondansetron sebagai Profilaksis Mual dan Muntah pada Pasien Kanker Payudara Stadium 3 Pasca Kemoterapi - Agustina Fitri Ariyani; Anita Purnamayanti; Aguslina Kirtishanti (Journal of Islamic Pharmacy, 2022)
Chemotherapy is one of the therapies used to reduce the risk of cancer cells metastases. Based on the mechanism of the drug, chemotherapy is an anti-neoplastic - which is toxic to the cancer and the normal cells. The adverse effects of chemotherapy comprise of myelosuppression, as well as nausea and vomiting. Therefore, patients are given prophylaxis antiemetics to prevent and reduce chemotherapy-induced nausea and vomiting (CINV). The aim of the study was to analyze the effectiveness of ondansetron as prophylaxis of nausea and vomiting in breast cancer patients. The design of this study was cohort observational study conducted prospectively. Breast cancer patients aged 20-80 years old who had been administered with one of combination cytotoxic regiments for 6 cycles on the first chemotherapy serial were involved in this study. We excluded breast cancer patients who were refused to be included in this study. The drop out criteria was subject who passed away before completing the full cycles. There were 76.7% subject of the study who experienced nausea or vomiting during and post chemotherapy, despite of ondansetron taken 8 mg orally in the full 6 cycles of the therapies. The result of the Multivariate test was that effectiveness of ondansetron in preventing CINV was not affected by body mass index (BMI) and age grouping (p=0.501). It could be concluded that the effectiveness of ondansetron in preventing CINV was not affected by the BMI as well as patients’ age.